Profil Keterampilan Komunikasi Ilmiah dengan Model Problem Based learning pada Materi Energi Terbarukan - Jumirta Agustina; Hadma Yuliani; Suhartono Suhartono (Kappa Journal, 2025)
Twenty-first century learning requires students to possess scientific communication skills as an essential ability to understand and convey scientific concepts. However, these skills are still relatively low, so an appropriate learning model is needed. The purpose of this study was to examine the effect of implementing the Problem Based Learning (PBL) model on renewable energy content toward students’ scientific communication skills. This research employed a pre-experimental method with a one group pretest-posttest design involving 33 tenth-grade students at SMAN 5 Palangka Raya. The instruments used were essay questions and assessment rubrics, and the data were analyzed descriptively and with N-Gain. The results indicated an increase in the average score from 45.55 to 66.27 with an N-Gain value of 0.37, categorized as moderate. Although some indicators showed only slight improvement, overall the conclusion is that the PBL model is effective in enhancing students’ scientific communication skills on renewable energy material.